Myofascial pain and treatment: Editorial a critical overview of the current myofascial pain literature – August 2019. Issue 4 (October 2019) - Dommerholt, Jan; Chou, Li-Wei; Hooks, Todd; Thorp, Jacob N.
Abstract: This quarter's overview of the myofascial pain literature includes quite a few basic research papers in addition to the usual high quantity of dry needling (DN) papers. Of particular interest are a study by Fischer and colleagues studying the role of mitochondrial functions in chronic trigger points (TrPs) (Fischer et al 2018 ), a study by Li and associates who conducted a quantitative proteomics analysis to identify biomarkers of chronic myofascial pain and therapeutic targets of dry needling in a rat model of TrPs (Li et al 2019 ), and a sonography study by Mitchell et al. looking into the distances from the skin to the pleura in the context of DN (Mitchell et al 2019 ). A total of 33 papers are included in this overview article. We welcome Dr. Jacob Thorp to our team of authors. Dr. Thorp is a US-based physical therapist. He is Professor and Founding Director of the Physical Therapy Program at Charleston Southern University in North Charleston, SC.